Performance Modelling and Analysis of Passive Optical Networks for Poisson Traffic - Vardakas, J. S.; Vassilakis, V. G.; Logothetis, M. D. (Communications - Scientific Letters of the University of Zilina, 2008)
Passive Optical Networks (PONs) are the most important class of fiber-based access systems, capable of delivering services with numerous applications, such as high-definition video and video conferencing. In this paper we perform call-level performance analysis of the upstream direction in TDMA-based PONs and hybrid TDMA-WDM PONs. The proposed analysis is based on well-established recursive teletraffic models and leads to Call Blocking Probabilities determination. We consider the case where the optical access network accommodates multiple serviceclasses with Poisson arriving calls. The accuracy of the proposed analytical models is validated by simulation and is found to be absolutely satisfactory.
Keywords: no keywords